2018
DOI: 10.1002/pola.29246
|View full text |Cite|
|
Sign up to set email alerts
|

Crosslinked colloids with cyclopropenium cations

Abstract: Chemical crosslinkers are commonly used to stabilize both natural and synthetic macromolecules, while providing opportunities to install functionality and modulate polymer architecture. Here, we introduce the aromatic cyclopropenium cation as a tri-functional crosslinker of secondary aminecontaining polymers. The one-step crosslinking reaction is rapid and requires no subsequent purification. When dispersed in aqueous media, the crosslinked polymers form spherical nanoparticles with highly positive charge that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In order to improve upon the transfection efficiency of PEI, a series of PEI nanoparticles was prepared by crosslinking with trisaminocyclopropenium (TAC). In a previous study [32], we showed that this crosslinking procedure provided cyclopropenium-crosslinked PEI nanoparticles upon dispersion into aqueous media ( Figure 1). We confirmed the presence of the cyclopropenium ring in the precipitate with 14c NMR and FTIR spectroscopy.…”
Section: Preparation Of Cyclopropenium-crosslinked Poly(ethylene Iminmentioning
confidence: 70%
See 2 more Smart Citations
“…In order to improve upon the transfection efficiency of PEI, a series of PEI nanoparticles was prepared by crosslinking with trisaminocyclopropenium (TAC). In a previous study [32], we showed that this crosslinking procedure provided cyclopropenium-crosslinked PEI nanoparticles upon dispersion into aqueous media ( Figure 1). We confirmed the presence of the cyclopropenium ring in the precipitate with 14c NMR and FTIR spectroscopy.…”
Section: Preparation Of Cyclopropenium-crosslinked Poly(ethylene Iminmentioning
confidence: 70%
“…Chloroform was purchased from Bio-Lab, Ltd. (Jerusalem, Israel). Crosslinking was performed as reported previously [32]. Briefly, TCC (10-60 mol%) was added dropwise to a 0.5 mM solution of PEI in chloroform at 0 • C. A white precipitate formed instantly, and the reaction was left to warm to room temperature and stirred overnight.…”
Section: General Crosslinking Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…XRD experiments showed several reflexes in the small-angle region. These were assigned as (10), (11), (04), (40), (42), (50), and (52) reflexes,i ndicating ac olumnar rectangular (Col r )m esophase with p2mm symmetry (Supporting Information, Figure S10). Derivative 10 a displayed an endothermal melting transition at 47 8 8Ca nd an endothermal clearing transition at 169 8 8Cu pon heating, and an exothermal crystallization at 5 8 8Cu pon cooling.T he isotropic to mesophase transition temperature of 169 8 8Cw as taken from POM experiments.U nder the POM, mosaic textures were observed (Figure 3c), suggesting either aplanar aligned columnar phase or alamellar phase.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[6] Most recent work has focused on their use as phase transfer, Lewis acid or organocatalysts, [7][8][9][10][11][12][13][14][15][16] electrophotocatalysts, [17] ligands for catalytic metal complexes, [18][19][20] ionic liquids, [21][22][23][24][25] persistent radical cations, [26] redox active polymers for redox flow batteries, [27][28][29][30][31][32] fluorescent materials, [33][34][35] aromatic cations in hybrid halide perovskites, [36] biologically active compounds such as transfection agents, [37][38][39] and nanoparticles. [40,41] Surprisingly, the self-assembly of cyclopropenium compounds into liquid crystalline phases has not been reported. [42] We hypothesized that mesomorphic self-assembly should be promoted by the planarity and charge delocalization of the aminocyclopropenium ion, which resembles an extended, or "deltic" guanidinium ion.…”
Section: Introductionmentioning
confidence: 99%